The divine names in Ibn 'Arabi's theory of oneness of existence - Sawai, Makoto (AUC Knowledge Fountain, 2014)
This thesis tries to consider Ibn ʿArabīʼs theory of Oneness of Existence (waḥdat al-wujūd), in terms of his argument of the divine names. It consists of the four chapters. The first chapter is to trace the descriptions of Ibn ʿArabī by Muslim scholars and scholars of Islamic studies. The second chapter discusses the idea of divine names in the context of the self-disclosure (tajallī) of Existence. The analysis in the third chapter is the divine presence (ḥaḍrah), and Ibn ʿArabIʼs explanation of the Mercy (al-Raḥmah) and the Lord (al-Rabb). In the fourth chapter, I consider the relationship between the Perfect Man (al-insān al-kāmil) and the divine names.